2014
DOI: 10.1007/978-3-319-10975-6_24
|View full text |Cite
|
Sign up to set email alerts
|

Amplification DDoS Attacks: Emerging Threats and Defense Strategies

Abstract: Part 2: 4th International Workshop on Security and Cognitive Informatics for Homeland Defense (SeCIHD 2014)International audienceThere are too many servers on the Internet that have already been used, or that are vulnerable and can potentially be used to launch DDoS attacks. Even though awareness increases and organizations begin to lock down those systems, there are plenty of other protocols that can be exploited to be used instead of them. One example is the Simple Network Management Protocol (SNMP), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For example, on February 10, 2014, about 1300 NTP servers on different networks were involved in an unprecedented cyber attack, where each server generated at peak hours approximately 90 Mb/s of traffic towards particular targets located on the Internet". [6] Figure 1: Distributed Denial of Service attack using NTP servers as reflectors [3] From Figure 1 above, it can be observed that the attacker successfully executed the DDoS amplified attack by sending a UDP/123 MONLIST request with a specific spoofed source address of the intended victim of the attack to a vulnerable NTP server. In return, the server then forwarded the reply to the spoofed IP address (the victim) and it was then flooded with large packets.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, on February 10, 2014, about 1300 NTP servers on different networks were involved in an unprecedented cyber attack, where each server generated at peak hours approximately 90 Mb/s of traffic towards particular targets located on the Internet". [6] Figure 1: Distributed Denial of Service attack using NTP servers as reflectors [3] From Figure 1 above, it can be observed that the attacker successfully executed the DDoS amplified attack by sending a UDP/123 MONLIST request with a specific spoofed source address of the intended victim of the attack to a vulnerable NTP server. In return, the server then forwarded the reply to the spoofed IP address (the victim) and it was then flooded with large packets.…”
Section: Related Workmentioning
confidence: 99%
“…"The goal of this type of honeypot is to lure an attacker to install either handler or agent code within the honeypot, thereby allowing the honeypot's owner to track the handler or agent behavior and better understand how to defend against future DDoS installation attacks. Honeypots are also helpful because they can store event logfiles during a DDoS attack" [6].…”
Section: Mitigating Ddos Ntp Amplified Attackmentioning
confidence: 99%
“…DDoS attacks can also be classified as Reflection and Amplification attacks. In a reflection attack, the size of the request and response is the same [41], whereas, in an amplification attack, the size of the response is many times bigger than that of the request [42]. In Table 6, the chronological evolution of DDoS attack vectors is depicted.…”
Section: A Distributed Denial Of Services (Ddos) Attacksmentioning
confidence: 99%
“…The Internet of Things (IoT) has made millions of computer devices connected via the internet network, thereby increasing security threats, including DDoS attacks [1] [2], and is the most noticed and most important attack on the Internet network today [3]. One such attack is the Simple Network Management Protocol (SNMP), a UDP protocol commonly used for network management so that a request sent to an SNMP server returns a larger response than an incoming request [4]. However, DDOS is one of the most prominent attacking behaviors over the network, which interrupts and blocks legitimate users from using network resources [5][6].…”
Section: Introductionmentioning
confidence: 99%